Designing an interpretative structural model for human resource agility. (18th November 2020) - Shahsavari-Pour, Nasser; Sayyadi-Tooranloo, Hossein; Pabarja, Elham; Heydarbeigi, Shahla
Nowadays, organisations act in an obscure, dynamic, and changing environment. One of the paradigms to deal with this changing environment is organisational agility. To achieve agility, the organisations need to develop agile staff to obtain the expected results; however, they always face problem regarding determining the factors affecting the agility of employees. Accordingly, this research aimed to identify the capabilities and empowerments of human agility. It also pursues an interpretive structural model of human resource agility, based on experiences of experts at the Vali-e-Asr University of Rafsanjan, Iran. After reviewing the literature and identifying the capabilities and empowerments of human agility, and including them in a semi-closed questionnaire based on the Likert spectrum, 43 experts responded to the questionnaire. After analysing the data and plotting an interpretive structural model for the capabilities and empowerments of human resources agility, a total of ten variables were identified in five levels.